LEGAL PROTECTION FOR CHILD VICTIMS OF VIOLENCE THROUGH LPSK IN THE CRIMINAL JUSTICE SYSTEM - Yola Iskandar; Bambang Widarto; Rizky Pratama Putra Karo Karo (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
The protection of children who are victims of violence is a constitutional obligation of the state as specified in Article 28B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. In the practice of the criminal justice system, child victims often experience multiple vulnerabilities such as intimidation, repeated trauma (revictimization), social stigma, and the lack of fulfillment of their rights to recovery and restitution. In this context, the Witness and Victim Protection Agency (LPSK) as an independent state institution plays a strategic role in ensuring the protection and fulfillment of the rights of child victims, as regulated in Law Number 31 of 2014 concerning the Protection of Witnesses and Victims and Government Regulation Number 43 of 2017 concerning the implementation of restitution for children who become victims of criminal acts. This research employs a normative legal research method using statutory, conceptual, and case approaches. The data consists of primary, secondary, and tertiary legal materials analyzed through qualitative juridical analysis. The study aims to examine the forms of legal protection provided by LPSK for child victims of violence within the criminal justice system and to identify obstacles in its implementation. The results show that LPSK provides protection including physical and psychological protection, legal assistance during judicial processes, medical support, psychological and psychosocial rehabilitation, and facilitation of restitution and compensation rights. However, several challenges remain, including weak restitution enforcement mechanisms, limited institutional resources, inadequate child-friendly facilities, suboptimal coordination among law enforcement agencies, and persistent victim-blaming attitudes within society.